Effect of the Gaseous Atmosphere in GaAs Films Grown by Close-Spaced Vapor Transport Technique - J. Jesús Cruz Bueno; Godofredo García Salgado; R. Fabiola Balderas Valadez; J. Alberto Luna López; F. Gabriela Nieto Caballero; Tomás Díaz Becerril; Enrique Rosendo Andrés; Antonio Coyopol Solís; Román Romano Trujillo; Crisóforo Morales Ruiz; J. Miguel Gracia Jiménez; Reina Galeazzi Isasmendi (Crystals, 2019)
The effect of the gaseous atmosphere in the growth of gallium arsenide (GaAs) films was studied. The films have been grown by close-spaced vapor transport (CSVT) technique in a home-made hot filament chemical vapor deposition (HFCVD) reactor using molecular hydrogen and molecular nitrogen as the transport agent. An important point about the gaseous atmosphere is the ease in creating volatile compounds when it makes contact with the GaAs source, this favors the transport of material in a CSVT system. Chemical reactions are proposed in order to understand the significant difference produced from the gaseous atmosphere. The films grown with hydrogen are (almost) continuous and have homogeneous layers with preferential orientation (111). The films grown with nitrogen are granular and rough layers with the coexistence of the orientations (111), (220) and (311) in the crystals. The incorporation of impurities in the films was corroborated by energy dispersive spectroscopy (EDS) showing traces of oxygen and nitrogen for the case of the samples obtained with nitrogen. Films grown in a hydrogen atmosphere show a higher band gap than those grown in a nitrogen atmosphere. With the results of XRD and micro-Raman we observe a displacement and broadening of the peaks, characteristic of a structural disorder. The calculations of the FWHM allow us to observe the crystallinity degree and determine an approximate crystallite size using the Scherrer’s equation.